HUBUNGAN PENGETAHUAN IBU TENTANG REAKSI KEJADIAN IKUTAN PASCA IMUNISASI DPT DENGAN TINDAKAN PEMBERIAN IMUNISASI DPT - Rani Kawati Damanik (Jurnal Keperawatan Priority, 2021)
Increasing immunization coverage is one way to reduce mortality in infants, especially in infectious diseases. along with increasing immunization coverage, can’t be separated from parental anxiety about reactions caused after the baby is immunized. The most serious occurrence Adverse Events Following Immunization (KIPI) in children is an anaphylactoid reaction estimated at 2 in 100,000 DPT doses, but actually anaphylactic reactions are only 1-3 cases among 1 million doses. The purpose of this study was to determine the relationship of maternal knowledge about Adverse Events Following Immunization (KIPI) with giving DPT immunization in the Work Area of ​​the health center UPT Matiti Medan in 2019. This study used descriptive research design with cross sectional approach with a population of 369 respondents so counter using the Sugiyono formula and the results obtained are 79 samples in the sampling using accidental sampling technique. The research instrument used a standardized questionnaire and the data obtained were analyzed by the Spearman rank test. The results of this study obtained from 79 respondents the majority of knowledgeable enough are 34 respondents (43.0%). And the majority of immunization is not given are 41 respondents (51.9%), then there is a strong relationship between mother's knowledge about the KIPI reaction with DPT immunization with p values ​​of 0.000 (<0.05) and the value of r = 0.577. The conclusion in this study is that there is a relationship between mother's knowledge about post-immunization (KIPI) follow-up reactions with DPT immunization, expected to mothers who have babies after knowing about the KIPI immunization reaction to always bring their babies to immunization in order to get immunity and avoid disease Diphtheria, Pertussis and Tetanus.